The Heartbeat of Innovation : A History of Cardiac Surgery at the Toronto General Hospital - Shorter, Edward; Goldman, Bernard S., 1936-; Scully, Hugh E. (Book collections on Project MUSE., 2022)
"Great innovations take place within great institutions. Founded in 1819, Toronto General Hospital (TGH) is one of Canada's oldest hospitals and has created a nurturing environment for early Canadian innovations in heart surgery. The Heartbeat of Innovation tells the story of the brilliant surgeons who worked there and the hospital environment that provided an incubator to the many people--skilled perfusionists, dedicated nurses, and pioneering cardiologists--who participated in the revolution in heart surgery that took place along University Avenue in Toronto. Supported by historical records, hospital archives, personal memoirs, and interviews, this book is an extensive and descriptive account of the seemingly inexorable development of cardiac surgery at this leading academic health science centre. It pursues several themes: the complexity of this surgical specialty, its generally male-dominated nature, the trend to teamwork in practice, and the evolution and incorporation of original research into this branch of healthcare. These strands are woven together to demonstrate how the TGH has evolved into such a dominant leader in the competitive and demanding field of cardiac surgery. Canadian hearts may beat with pride at the knowledge that one of the major stories in modern medicine took place here--and continues here."--